"Border closure only increased precariousness": a qualitative analysis of the effects of restrictive measures during the COVID-19 pandemic on Venezuelan's health and human rights in South America - Teresita Rocha-Jimenez; Carla Olivari; Alejandra Martínez; Michael Knipper; Báltica Cabieses (BMC, 2023)
Abstract Background In 2010, a political and social crisis pushed thousands of Venezuelans out of their country; today, seven million Venezuelans live abroad. In addition, during the COVID-19 pandemic, border closure increased and affected specific vulnerable migration flows, such as Venezuelans trying to migrate to Chile through the Northern borders. In this context, there is little evidence of migrants' health status and needs, their access to health services, and other basic needs (e.g., housing) from a human rights perspective. Therefore, we qualitatively explored the effects of border closure due to the COVID-19 pandemic on Venezuelan migrants' health and human rights, focusing on access to healthcare in the Northern Chilean border that adjoins Peru and Bolivia. Methods Following a case-study qualitative design, we conducted an ethnography that included participatory observation of relevant sites (e.g., hospitals, main squares, migrant shelters) in Antofagasta, Iquique, and Arica and 30 in-depth interviews with actors in the health sector (n = 7), experts from the non-governmental sector (n = 16), and governmental actors (n = 7) in three large cities close to the Northern border. Results We found four main dimensions: (i) border and migration processes, (ii) specific groups and intersectionality, (iii) barriers to healthcare services, and (iv) regional and local responses to the crisis during the COVID-19 pandemic. Programs characterized by the presence of healthcare providers in the field were essential to attend to migrants' health needs at borders. Conclusions Coordination between actors is crucial to implement regional protocols that respond to current migration phenomena and migrants' health needs. Health policies using a human rights approach are urgently required to respond to migrants' healthcare needs at borders in South America.